Assessment tools PKM Model Involving Scaffolding Metacognitive Based on Revised Bloom's Taxonomy - Awi, Awi; Sukarna, Sukarna (Indonesian Journal of Educational Studies, 2013)
This research aims to develop software process assessment and the results of applying the model statistics PKM-BC material. The study was designed with the development of the Model Plomp. The test device of assessment will be conducted at SMAN 11 and SMAN 3 Makassar.Untuk achieve the objectives of this study used a method of development of Plomp (1997), which consists of five phases. Based on research, the resulting asesen valid, practical, and effective. The resulting assessment device includes four dimensions of knowledge, that is faktual, konseptuap, procedural, and metacognitive.